Companion Plants of Tea: From Ancient to Terrace to Forest - Huan Wu; Xiaofeng Long; Yanfei Geng (Plants, 2023)
China is one of the origins of ancient tea gardens, with a long history of tea culture and tea cultivation. Guizhou Province is an important tea production place in southwest China with rich forest tea resources. The purpose of this study is to obtain historical information on companion plants in historical tea gardens and provide a theoretical basis for the sustainable development of forest tea gardens in Guizhou Province. We conducted a statistical analysis and comparison of plant species among ancient tea gardens, terrace tea gardens, and forest tea gardens from a diachronic perspective, based on 21 ancient tea literature studies, 116 terrace tea garden documents, and 18 sampled plots of forest tea gardens in Guizhou. A total of 24 companion plants species belonging to 16 families and 22 genera were found in ancient tea gardens, 81 species were found in terrace tea gardens belonging to 37 families and 74 genera, and 232 species were found in sample plots of forest tea gardens belonging to 90 families and 178 genera. Companion plants can be divided into three categories. Most of the plant families recorded in the literature also appeared in the forest tea garden we surveyed. In ancient tea gardens, terrace tea gardens, and forest tea gardens, Poaceae, Fabaceae, and Rosaceae were the most dominant families, respectively. The intercropping of tea gardens has been practiced since ancient times. Companion plants in natural forest tea gardens not only provide important insights into intercropping of terrace gardens but also hold significant implications for the conservation of existing forest tea gardens and the sustainable development of tea gardens.